2010
DOI: 10.3109/14659891.2010.519421
|View full text |Cite
|
Sign up to set email alerts
|

The influence of parents and friends on adolescent substance use: a multidimensional approach

Abstract: The current study examined longitudinal associations between friend’s substance use, friendship quality, parent-adolescent relationship quality and subsequent substance use. Participants were 166 adolescents, their parents and their close same-sex friends. Measures of relationship characteristics in the 10th grade were used to predict concurrent substance use and changes in substance use over a one-year period. The most consistent predictor of the use of different substances and changes in substance use over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
74
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 31 publications
10
74
1
3
Order By: Relevance
“…In other words, the variance in relationship quality that predicted later substance use tended to be shared with early substance use. This study thus provides some support for the notion that the parent-adolescent relationship in early adolescence can be predictive of later substance use [14][15][16], and that prior work on the topic, mostly based on European American or European samples, generalizes to Mexicanorigin youth.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In other words, the variance in relationship quality that predicted later substance use tended to be shared with early substance use. This study thus provides some support for the notion that the parent-adolescent relationship in early adolescence can be predictive of later substance use [14][15][16], and that prior work on the topic, mostly based on European American or European samples, generalizes to Mexicanorigin youth.…”
Section: Discussionsupporting
confidence: 67%
“…Meta-analytic evidence indicates that a positive parent-adolescent relationship predicts later initiation of alcohol use, and less problematic alcohol use later in life [14]. There is also evidence that parent-adolescent relationship quality predicts future use of tobacco, marijuana, and other illicit substances [15,16]. Moreover, intervention programs that improve the quality of the parent-child relationship have been shown to delay the onset and reduce the rate of substance use [17].…”
Section: Introductionmentioning
confidence: 99%
“…More EMC is thus associated with more FTF interactions. As a consequence, their own substance use likely increases, given the well-established fact that adolescents often engage in substance use in the presence of peers and the fact that peer substance use predicts adolescents own substance use (e.g., Branstetter et al 2011;Chassin et al 2009;Duncan et al 2006;Rai et al 2003). However, the associations between EMC and adolescent substance use should not be interpreted as solely a result of frequent FTF interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviorally based theories of influence suggest that adolescents emulate the behaviors of their friends following friends' social reinforcements (Piehler 2011;Prinstein and Dodge 2008). In line with this, it is well established that hanging out with friends is related to adolescent substance use (Branstetter et al 2011;Chassin et al 2009;Duncan et al 2006;Rai et al 2003). Frequent FTF interactions with friends in the evening in particular were strongly associated with various forms of substance use (Kuntsche et al 2009a).…”
Section: Introductionmentioning
confidence: 86%
“…3 Drugs use among teenagers is one of the significant public health concerns. 4 A survey conducted at Minnesota 5 in 2011 showed that most of drugs users were 11-12 graders. Ricardo 6 stated that the number of drug users was increasing.…”
Section: Introductionmentioning
confidence: 99%